THE EFFECTIVENESS OF MODERN TECHNOLOGIES IN TEACHING CHEMISTRY (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The use of modern technologies in teaching chemistry has revolutionized the way the subject is taught and learned. With advancements in digital tools, simulation software, and virtual labs, both students and educators are able to explore complex chemical concepts more interactively and engagingly.